Interventions to enhance return-to-work among young and middle-aged cancer survivors: a systematic review - ZHANG Yuanyuan; WU Anqi; WU Jie; ZHU Yaqi; LI Mengyao; YAN Dexiu; ZHANG Yaqing; HOU Lili (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To systematically evaluate the application of return-to-work intervention programs to young and middle-aged cancer survivors and its effectiveness in improving work-related outcomes in cancer survivors.Methods·An initial literature search of eight electronic databases, including PubMed, Cochrane Library, Embase, CNKI and Wanfang was conducted with a time frame from inception to Aug 2nd, 2022 to collect randomized controlled trials (RCTs) and quasi-experimental studies of return-to-work interventions on work-related outcomes among cancer survivors. Two researchers independently conducted literature screening, data extraction, and methodological quality evaluation using the JBI (Joanna Briggs Institute) Methodology Quality Evaluation Tool.Results·A total of 13 original studies were included, involving 11 return-to-work intervention programs, containing 2 045 cancer survivors. The results of the systematic evaluation showed that 10 of the intervention programs were multidisciplinary, with intervention modules on disease/mental health education, group discussions, physical rehabilitation, work capacity exercises, multidisciplinary team meetings and counselling. Among them, three interventions also included employers in the support program. The duration of the interventions ranged from 7 d to one year. Eight of the included interventions took return-to-work rates as a primary outcome, but only three reported that the difference was statistically significant, two of which were quasi-experimental studies without control group. Besides, no clear positive effects were found on work-related outcome such as length of return-to-work, change of work status, work ability, and work meaning.Conclusion·The content, format, intensity and frequency of return-to-work intervention programs for cancer survivors vary widely, and the effects of interventions on work-related outcomes are still unclear. Researchers should further explore the mechanisms that influence cancer survivors′ return-to-work, and develop multidisciplinary intervention programs based on this to effectively help young and middle-aged cancer survivors return-to-work and society. In addition, due to the limitations of study quality and intervention program heterogeneity, more high-quality experimental studies are needed to further validate the above findings.